Electrophysiological comparison of left versus right stellate ganglia neurons - Arie O. Verkerk; Carol Ann Remme; Molly O'Reilly (Journal of Molecular and Cellular Cardiology Plus)
Background: The stellate ganglia of the peripheral autonomic nervous system innervate the heart and continuously fine-tune cardiac function to meet physiological demands. The right stellate ganglion (RSG) predominantly innervates the sinoatrial node and has functional effects on chronotropy/heart rate, whereas the left stellate ganglion (LSG) has predominance in the ventricular myocardium and impacts inotropy/contractility. Whilst the innervation patterns and functional consequences of block and stimulation are well-documented, basic electrophysiological characterisation and single-cell comparison of RSG and LSG neurons has not been performed. In addition, sex differences in stellate ganglion action potential (AP) parameters may exist, but remain as yet unknown. Methods/results: Here we characterise the electrical properties of enzymatically isolated mouse stellate ganglia neurons using the patch clamp technique. Using 500 ms depolarising pulses of varying amplitude, we provide detailed characterisation of basic AP properties and their correlations. We reveal that there are two populations of neurons in terms of their AP firing properties (phasic or tonic firing), with the majority (65 %) firing with a phasic pattern. When all recordings were pooled, tonic neurons had a significantly larger AP amplitude (85 ± 3.0 vs 76 ± 2.4 mV) and overshoot (28 ± 1.8 vs 19 ± 1.8 mV) compared to phasic neurons (P < 0.05). Moreover, phasic neurons did not fire spontaneously, whereas 50 % of tonic neurons did, and more often presented with anodal break excitation (P < 0.05). When male vs female neurons were compared (with LSG and RSG neurons as subgroups), males had a more negative minimum diastolic potential (MDP; −55 ± 1.7 vs −47 ± 3.0 mV, P < 0.05) and higher percentage of anodal break excitation (P ≤ 0.05). When LSG vs RSG neurons were compared (with gender as subgroups), no significant differences were observed except a higher percentage of anodal break excitation in the RSG (P ≤ 0.05). Conclusions: Isolated RSG and LSG neurons have similar AP firing patterns and properties. A significant difference was observed in the MDP and anodal break excitation of male vs female neurons. However, all other AP parameters were similar. This suggests that the LSG and RSG can be combined irrespective of sex when investigating the electrophysiological properties of these distinct anatomical structures.